Syntax overview at units’ level: Syntagma, sentence, phrase, and some correlations with the order of Greek-Albanian constituents in Th.Mitko’s Phrase Book (1887-1888) - Bramo, Elvis (European Journal of Multidisciplinary Studies, 2017)
: In the article “Syntax overview at units’ level: Syntagma, sentence, phrase, and some correlations with the order of their Greek-Albanian constituents in the tri-lingual Talking Dictionary of Th. Mitko”, the author, pedagogue of the Modern Greek Language in the University of Tirana, Elvis Bramo, brings the level of the language as the main topic of this research, that is the syntactical level, starting from the syntagma unit (as a building unit), different types of sentences, some phrases with predicative components, and some bilingual segments: Albanian-Greek, to identify several peculiarities of word order. This comparative study between the two languages ( the Talking Dictionary has been compiled in three languages) aims at achieving some partial conclusions about the construction of the syntagma, their types as far as syntax connecting ways are concerned, and the valences that merge them into classes of words; It aims to identify the types of sentences with the grammatical elements of the question, with question words, with the denial grammatical tools, as well as the characteristics of the verbs as the heart of the syntatical organization in the communicated unit-phrase. Regarding the phrase (period), Bramo has pointed out the relationship of the phrasal components merging, their functioning together with their thematic and rematic role, on the basis of the Prague School. The language research from this viewpoint of Th.Mitko’s work, one of the most famous Albanian folklorists, has also brought in a comparable plan some models of syntactical phrasal and compound structures, to show that although the Greek and the Albanian languages are natural languages with a free word order (SVO), they do have parametric changes regarding the consituent parts of the sentence, particularly in the connoted constructions.